Antiviral Activity of Interferon Alpha-Inducible Protein 27 Against Hepatitis B Virus Gene Expression and Replication - Ullah, Hafiz; Sajid, Muhammad; Yan, Kun; Feng, Jiangpeng; He, Miao; Shereen, Muhammad Adnan; Li, Qiaohong; Xu, Tianmo; Hao, Ruidong; Guo, Deyin; Chen, Yu; Zhou, Limin; et al. (Frontiers in Microbiology, 2021)
Despite the availability of effective vaccines, hepatitis B virus (HBV) is still a major health issue, and approximately 350 million people have been chronically infected with HBV throughout the world. Interferons (IFNs) are the key molecules in the innate immune response that restrict several kinds of viral infections via the induction of hundreds of IFN-stimulated genes (ISGs). The objective of this study was to confirm if interferon alpha-inducible protein 27 (IFI27) as an ISG could inhibit HBV gene expression and DNA replication both in cell culture and in a mouse model. In human hepatoma cells, IFI27 was highly induced by the stimulation of IFN-alpha (IFN-α), and it potentiated the anti-HBV activity. The overexpression of IFI27 inhibited, while its silencing enhanced the HBV replication in HepG2 cell. However, the knocking out of IFI27 in HepG2 cells robustly increases the formation of viral DNA, RNA, and proteins. Detailed mechanistic analysis of the HBV genome showed that a sequence [nucleotide (nt) 1715–1815] of the EnhII/Cp promoter was solely responsible for viral inhibition. Similarly, the hydrodynamic injection of IFI27 expression constructs along with the HBV genome into mice resulted in a significant reduction in viral gene expression and DNA replication. In summary, our studies suggested that IFI27 contributed a vital role in HBV gene expression and replication and IFI27 may be a potential antiviral agent for the treatment of HBV.